2000
DOI: 10.1034/j.1600-0404.2000.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of conserved aspartates affect maturation of presenilin 1 and presenilin 2 complexes

Abstract: Presenilin (PS1 and PS2) holoproteins are transiently incorporated into low molecular weight (MW) complexes. During subsequent incorporation into a higher MW complex, they undergo endoproteolysis to generate stable N‐ and C‐terminal fragments (NTF/CTF). Mutation of either of two conserved aspartate residues in transmembrane domains inhibits both presenilin‐endoproteolysis and the proteolytic processing of APP and Notch. We show that aspartate‐mutant holoprotein presenilins are not incorporated into the high mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 41 publications
4
42
0
Order By: Relevance
“…This is consistent with our observation that surplus CTF is not physically associated with the dimer. It will be of interest to determine whether excess CTF produced upon inhibition of GSK-3␤ phosphorylation is present in the mature ϳ250-kDa 2 F. Kirschenbaum molecular mass complex or in the immature ϳ180-kDa complex described by Yu et al (9,11) and Capell et al (10). The regulation of PS1 CTF levels by GSK-3␤ is similar, if not identical, to the regulation of ␤-catenin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with our observation that surplus CTF is not physically associated with the dimer. It will be of interest to determine whether excess CTF produced upon inhibition of GSK-3␤ phosphorylation is present in the mature ϳ250-kDa 2 F. Kirschenbaum molecular mass complex or in the immature ϳ180-kDa complex described by Yu et al (9,11) and Capell et al (10). The regulation of PS1 CTF levels by GSK-3␤ is similar, if not identical, to the regulation of ␤-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…Endoproteolysis of the 46-kDa PS1 holoprotein to a heterodimer composed of 20-kDa CTF and 30-kDa NTF has been linked to the stabilization of PS1 (6, 7, 13), to its incorporation into a high molecular weight complex (9, 10), and to its maturation as a functional entity (11). In this mature stable state, the PS1 dimeric struc- Twenty-four hours post-transfection, cell extracts were prepared, and PS1 protein levels were assessed by Western blot with an anti-His monoclonal antibody for fulllength PS1 holoprotein and CTF and with the Chemicon antibody for NTF.…”
Section: Discussionmentioning
confidence: 99%
“…4B, lane 5). The PS1 D385A and PS1 D257A mutations and the equivalent mutations in PS2 were shown previously to generate only the intermediary, ϳ180-kDa, immature, non-functional complexes containing holoprotein (25), which do not mature into the higher molecular weight (Ͼ Ͼ250 kDa) functional complex containing PS1-NTF/CTFs (25). The apparently larger amount of APH-1 1 L co-immunoprecipitated with PS1 D385A compared with wild type PS1 (Fig.…”
Section: Fig 2 Western Blot Analysis Of Endogenous and Transfected mentioning
confidence: 99%
“…The evidence for this view includes the following observations. 1) D257A PSEN1, which could not restore neurotrypsin up-regulation induced by the double deficiency, is incapable of endoproteolytic cleavage and is unable to assemble into a mature ␥-secretase complex (40). 2) The uncleavable ⌬E9 hPSEN1 mutant form, which is still able to associate and form a mature ␥-secretase complex (41), efficiently restored neurotrypsin expression in Psen1/2 dKO cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although these results may suggest a ␥-secretase-independent mechanism to regulate neurotrypsin expression, previous studies revealed that drug inhibitors of ␥-secretase are not necessarily equally efficient in block- ing all ␥-secretase-dependent activities (36 -38). Therefore, to unambiguously test whether ␥-secretase is involved in this process, we took advantage of the catalytically dead D257A hPSEN1 mutant, which is unable to undergo autocatalytic endoproteolytic cleavage and unable to form a mature high molecular weight active ␥-secretase complex (39,40). As expected, unlike reintroduction of wild-type hPSEN1/2, reintroduction of D257A hPSEN1 and wild-type hPSEN2 into Psen1/2 dKO cells showed no detectable PSEN1 CTFs or mature nicastrin (Fig.…”
Section: Tg-prss12 Thymentioning
confidence: 99%